Caiva cittāntac celvarākiya Śrīmat Cokkaliṅka Aiyar avarkaḷ carittiram - Irāmacāmic Ceṭṭiyār, Rāma. U., 1872-1938 (SAMP early 20th-century Indian books project ;, 1935)
On the life of Cokkaliṅka Aiyar, Śaivite leader.